Cover Image, Volume 231, Number 8, August 2016. Issue 8 (August 2016) - Mittal, Rahul; Chan, Brandon; Grati, M'hamed; Mittal, Jeenu; Patel, Kunal; Debs, Luca H.; Patel, Amit P.; Yan, Denise; Chapagain, Prem; Liu, Xue Zhong
Abstract : Cover : The cover image, by Xue Liu et al., is based on the Review Article Molecular Structure and Regulation of P2X Receptors With a Special Emphasis on the Role of P2X2 in the Auditory System, DOI:10.1002/jcp.25274 .